Capacity Building to Achieve Sustainable Development Goals (SDGS) in Reduce Maternal and Infant Mortality Rate (Study in the Organizational Scope of Regional Development of Timor Tengah Selatan) - Hendrik TODA; Maria LINO; Dominikus FERNANDES; Markus TAE (Indonesia Strategic Sustainability, 2023)
The Regional Government of South Central Timor Regency is fully aware of and knows what the SDGs are. Some OPD leaders and officials know the SDGs are only an extension of the MDGs, but do not know the substance of the agenda. The method used in this study is a descriptive method with a qualitative approach, then the primary data and secondary data collected are analyzed using data analysis techniques from Creswell (2016). Capacity building in order to achieve sustainable development goals (SDGs) in reducing maternal and infant mortality within the scope of the South Central Timor Regency Regional Apparatus Organization uses the opinion of Thompson (2003: 60) which develops the concept created by Parsons (1960 with research results namely on ;( a) at the technical level it was found that the Regional Apparatus Organization (OPD) in TTS Regency did not yet have a comprehensive understanding of the SDGs with indicators of maternal and infant mortality so that they were still limited to the problem of stunting alone and still had problems integrating databases in each agency.(b) level managerially it was found that there was no synchronization of personnel allocation for each unit and function in carrying out SDG's goals (c) at the institutional level it was known that local governments had not developed effective policies regarding the implementation of SDGs in regional development plans.